Anti-proliferative activity and characterization data on oxadiazole derivatives - Dukanya; Muthu K Shanmugam; Shobith Rangappa; Prashant K Metri; Surender Mohan; Basappa; Kanchugarakoppal S Rangappa (Data in Brief, 2020)
This data in brief article explains the anti-cancer activity and characterization of oxadiazoles [1]. The main objective of this article was to provide general synthetic procedures, spectral discussion and physical data on the new oxadiazole tethered indazole (OTDs). This article discusses the 1H NMR, 13C NMR, mass spectroscopy, HPLC and melting point of the synthetic compounds. MTT assay was used to determine the anti-proliferative activity in hepatocellular cell lines.